Climate change will affect hydrological regimes in the Alps - Gabriele Confortola; Andrea Soncini; Daniele Bocchiola (Revue de Géographie Alpine)
Climate change will affect hydrological cycle and water resources in the Alps. Here we sketched potential future (2045-2054) hydrological cycle under prospective climate change scenarios within an Alpine river of Italy: Serio (ca. 300 km2). Therein, hydrology is highly dependent upon snow cover cycle, very likely to be affected by climate changes. We set up and validated a hydrological model able to mimic water resources regime of the river. We then use downscaled future temperature and precipitation from two general circulation models GCMs to feed the hydrological model and obtain projected hydrological regimes, at flow sections at different altitudes within the catchment. The scenarios and storylines from the adopted GCMs differ from one another with respect to projected precipitation and temperature amount, but agree upon decrease of the former and increase of the latter. All hydrological scenarios agree upon prospective shrinkage of seasonal snow cover due to increased temperature, and upon prospective increase of Fall and Winter stream flows as due to increased liquid precipitation. Lower discharges are projected during Spring and Summer, in view of decreased rainfall and snow cover at thaw, and the CCSM3 model provides shifting of thaw season to one month earlier. Higher catchments are more impacted because Winter flows increase more proportionally.